Analisis Pengaruh Rasio Keuangan Early Warning System Tingkat Suku Bunga Sertifikat Bank Indonesia Dan Price To Book Value Terhadap Harga Saham Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia - Elina Rahmawati Gustarina; Sri Elviani; Muhammad Joni Barus; Kardila Maysuri (Universitas Islam Islam Sumatera Utara, 2023)
The problem in this study is whether the Early Warning System's financial ratios namely fund adequacy ratios, underwritting ratios, claims expense ratios, liquidity ratios, premium growth ratios, retention ratios, SBI interest rates and Price to Book Value simultaneously affect stock prices at insurance company listed on the Indonesia Stock Exchange. This study aims to determine whether there is an influence of fund adequacy ratios, underwritting ratios, claims expense ratios, liquidity ratios, premium growth ratios, retention ratios, SBI interest rates and price to book value to stock prices on insurance companies listed on the Indonesia Stock Exchange. The sample selection was carried out using the purposive sampling method and sources of data in this study are secondary data obtained from the sites www.idx.co.id and www.sahamok.com. Data processing is done by pooling data. The analytical method used is multiple regression analysis with the help of SPSS 22. The results showed simultaneously (Test F) that independent variables significantly influence stock prices. This can be seen from the calculated F value (6.871) F table (2.46) and α 0.000 0.05.